2003
DOI: 10.1590/s1677-55382003000600012
|View full text |Cite
|
Sign up to set email alerts
|

Pubovaginal sling in the treatment of stress urinary incontinence for urethral hypermobility and intrinsic sphincteric deficiency

Abstract: Purpose: This study was undertaken to evaluate the use of pubovaginal sling for the treatment of female stress urinary incontinence in patients with intrinsic sphincteric deficiency and patients with urethral hypermobility.Materials and Methods: Sixty-two patients aging 22 to 73 years-old (mean = 49.6) with a median parity of 4.1 (range 0 -14) who underwent pubovaginal autologous fascial sling procedures for stress urinary incontinence from August/1999 to August/2002 were prospectively analyzed. Objective pre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Studies comparing commercially available synthetic slings with the pubovaginal fascial sling or Burch's colposuspension (13)(14)(15)(16)(17) have shown that these slings are promising, but there is still the question of cost, which is prohibitive in our situation. The option of an aponeurotic sling either from the rectus abdominis or a polypropylene mesh for the surgeon to use to construct the sling appears to be an accessible procedure, and the cost is compatible with the conditions in our clinical working environment.…”
Section: Commentsmentioning
confidence: 99%
“…Studies comparing commercially available synthetic slings with the pubovaginal fascial sling or Burch's colposuspension (13)(14)(15)(16)(17) have shown that these slings are promising, but there is still the question of cost, which is prohibitive in our situation. The option of an aponeurotic sling either from the rectus abdominis or a polypropylene mesh for the surgeon to use to construct the sling appears to be an accessible procedure, and the cost is compatible with the conditions in our clinical working environment.…”
Section: Commentsmentioning
confidence: 99%
“…[9] Indications Currently, PVS procedures are used primarily to treat patients with intrinsic sphincter dysfunction from a variety of difference causes. [10][11][12] However, recent studies support the notion that the PVS can be used as the primary surgical method in all of the cases of SUI. [13][14][15] PVS procedures can be successfully performed in patients with mixed urinary incontinence, neuropathic disorders that result in the loss of the closing function of the proximal urethra, acquired conditions such as a urethral diverticulum that may result in tissue loss when repaired, urethral erosions caused by a synthetic material or an artificial sphincter, and in patients who previously underwent unsuccessful incontinence surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Some years ago, some reports showed up demonstrating good results for all types of female stress urinary incontinence as well (2)(3)(4). This major indication of the technique has been accompanied by incidences of prolonged urinary retention of 5 to 20% (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%